2016
DOI: 10.1186/s12870-016-0705-8
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic acid treatment and expression of an RNA-dependent RNA polymerase 1 transgene inhibit lethal symptoms and meristem invasion during tobacco mosaic virus infection in Nicotiana benthamiana

Abstract: BackgroundHost RNA-dependent RNA polymerases (RDRs) 1 and 6 contribute to antiviral RNA silencing in plants. RDR6 is constitutively expressed and was previously shown to limit invasion of Nicotiana benthamiana meristem tissue by potato virus X and thereby inhibit disease development. RDR1 is inducible by salicylic acid (SA) and several other phytohormones. But although it contributes to basal resistance to tobacco mosaic virus (TMV) it is dispensable for SA-induced resistance in inoculated leaves. The laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 71 publications
3
57
0
1
Order By: Relevance
“…Moreover, it was shown that transgenic NtRDR1 antisense tobacco plants are more susceptible to TMV infection than wild-type plants (Xie et al, 2001). There are many reports demonstrating the role played by RDR1 and RDR6 in the defence against viruses (Pandey and Baldwin, 2007;Liu et al, 2009;Rakhshandehroo et al, 2009;Qin et al, 2012;Liao et al, 2014;Lee et al, 2016). Thus, there are several reports which support the RDR1 contribution to the antiviral defence mechanism during Tobamovirus infections.…”
Section: Rna Interference-mediated Resistancementioning
confidence: 98%
See 2 more Smart Citations
“…Moreover, it was shown that transgenic NtRDR1 antisense tobacco plants are more susceptible to TMV infection than wild-type plants (Xie et al, 2001). There are many reports demonstrating the role played by RDR1 and RDR6 in the defence against viruses (Pandey and Baldwin, 2007;Liu et al, 2009;Rakhshandehroo et al, 2009;Qin et al, 2012;Liao et al, 2014;Lee et al, 2016). Thus, there are several reports which support the RDR1 contribution to the antiviral defence mechanism during Tobamovirus infections.…”
Section: Rna Interference-mediated Resistancementioning
confidence: 98%
“…Orthologous genes of NtRDR1 have also been characterized in other species, such as Nicotiana glutinosa (NgRDR1), Nicotiana benthamiana (NbRDR1m), A. thaliana (AtRDR1), Medicago truncatula (MtRDR1) and rice (OsRDR1), all of them being induced by both viral infection and SA treatment (Yu et al, 2003;Yang et al, 2004;Quilis et al, 2008;Liu et al, 2009). Several findings indicate that RDR1 could be involved in the SA-induced resistance against viruses (Alamillo et al, 2006;Lee et al, 2016). The impact of SA on the modulation of RDR1 action was demonstrated in tobacco NahG transgenic plants infected with PPV.…”
Section: Rna Interference-mediated Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, non-host resistance is likely due to an intrinsic lack of susceptibility, which is a multigenic trait. It is now known that natural compounds, such as melatonin that modulate immune responses, such as ROS metabolism, calcium signaling and mitogen-activated protein kinase (MAPK) cascades, can be used to enhance natural resistance [106]. Notably, the recent identification and functional analysis of melatonin synthesis genes in cassava has provided a direct link between melatonin and immune responses [107].…”
Section: Natural Pathogen Resistance and Cassava Virus Controlmentioning
confidence: 99%
“…In the interaction between viruses and phytohormones, RNA-dependent RNA polymerase ( RDR ) family is involved in the establishing of the resistance in host plants. In MtRDR1 transgenic tobaccos, MtRDR1 can function as RDR6 and can help the host plants to recover from the symptom caused by virus infection in the presence of SA (Lee et al, 2016). …”
Section: Introductionmentioning
confidence: 99%